2021
DOI: 10.3390/healthcare9111526
|View full text |Cite
|
Sign up to set email alerts
|

Association between Psychological Stress and Neck Pain among College Students during the Coronavirus Disease of 2019 Pandemic: A Questionnaire-Based Cross-Sectional Study

Abstract: The coronavirus disease of 2019 (COVID-19) greatly affected people’s lifestyles. We used an online, cross-sectional survey during a COVID-19-related lockdown in Israel, with the aim of investigating the effects of such lockdowns on students’ self-perceived stress and neck pain (NP). College students (N = 295) completed questions on sociodemographic characteristics, the Neck Disability Index (NDI), the Perceived Stress Scale, the Visual Analogue Scale (VAS), and NP frequency (four-point scale). Logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
1
14
0
1
Order By: Relevance
“…Three studies [34,44,47] analyzed the effects of high pressure on neck pain among college students. The combined results showed that the greater the pressure, the more likely they were to cause neck pain, with minimal heterogeneity (OR = 1.91, 95% CI: 1.50 to 2.42, P < 0.00001, I 2 = 0%) (Fig.…”
Section: High Pressurementioning
confidence: 99%
“…Three studies [34,44,47] analyzed the effects of high pressure on neck pain among college students. The combined results showed that the greater the pressure, the more likely they were to cause neck pain, with minimal heterogeneity (OR = 1.91, 95% CI: 1.50 to 2.42, P < 0.00001, I 2 = 0%) (Fig.…”
Section: High Pressurementioning
confidence: 99%
“…Based on research conducted by Daher (2021), they found that neck pain among college students during lockdown was higher than in the previous period, and the neck pain appearance was associated with the Visual Analogue Scale (VAS) score and the NDI questionnaire. 9 Therefore, the researchers hypothesized that the prevalence of neck pain among undergraduate physiotherapy students at Udayana University was higher during the pandemic. The present study is designed to investigate the relation between the duration of laptop usage and neck disability.…”
Section: Original Articlementioning
confidence: 99%
“…The funnel plot depicted bilateral asymmetry and, therefore, a possible publication bias (Figure 3). Three studies [34,44,47] analyzed the effects of high pressure on neck pain among college students. The combined results showed that the greater the pressure, the more likely they were to cause neck pain, with minimal heterogeneity (OR=1.91, 95% CI: 1.50 to 2.42, P<0.00001, I 2 =0%) (Figure 2I).…”
Section: Long-time To Bow Headmentioning
confidence: 99%